Pemanfaatan Ekstrak Jagung (Zea Mays) di Kabupaten Grobogan Dalam Bentuk Sediaan Gel Sebagai Pelindung dari Sinar UVB: Array - Gigih Kenanga Sari; Mauilita Saraswati (Pratama Medika : Jurnal Kesehatan, 2022)
The purpose of this study was to produce a gel preparation with corn kernel extract as raw material, product profile information and the safety effects of using corn kernel extract gel preparation. The method used in this study with corn extract formulated into HPMC base with concentrations of 5%, 10%, and 20%. Then performed physical testing, the effect of the gel in rabbits and on the skin of human hands. This research produces a gel preparation with corn kernel extract as the raw material. The gel produced by increasing the concentration of HPMC can increase the viscosity, stickiness, and decrease the spreadability, but the increase in the concentration of HPMC does not affect the pH. The results of the effect test on the skin showed that corn extract gel could function as a skin protector from the sun, but the difference in HPMC concentration did not give a difference in the effect of protecting the skin from the sun. This study resulted in a conclusion in the form of a gel preparation with corn kernel extract as raw material, the product profile increased viscosity, gel adhesion, and also decreased dispersion, but the increase in HPMC concentration did not affect the pH of the preparation and the gel was safe as a skin protector from the sun.